Telluric Field Variations as Drivers of Variations in Cathodic Protection Potential on a Natural Gas Pipeline in New Zealand. Issue 9 (25th September 2018) - Ingham, M.; Rodger, C. J.
Abstract: A study of variations in cathodic protection potential on a natural gas pipeline in the North Island of New Zealand is reported. Both the measured pipe‐to‐soil potential (PSP) and the current measured through an installed defect in the pipeline coating show strong correlations with variations in measured magnetic and telluric fields. Contrary to predictions from distributed‐source transmission line theory, analysis shows that the closest correlations of PSP and current are with the component of telluric field perpendicular to the pipeline. This orientation is close to perpendicular to major electrical conductivity contrasts associated with both the local coastline and with on‐shore Earth conductivity structure. It is therefore inferred the variations in PSP which drive the variations in defect current are the result of changes in the local Earth potential. While reporting on specific observations from New Zealand, these results should be applicable across a wide range of middle and high‐latitude global locations. Estimates of possible corrosion rates for the pipeline in question suggest that such enhancement of telluric field variations by conductivity structure may pose significant risk to pipelines in the event of defects in the pipeline coating. Plain Language Summary: Temporal variations in Earth's magnetic field induce electric fields in the ground. Rapid and large changes in the magnetic field, such as during magnetic storms, can produce earth currents that can have a significant impact on technological systems such as power transmission lines and oil and gas pipelines. Pipelines generally have an insulating coating. Should a break in this occur, electrochemical reactions can allow a current to pass from the pipe to the ground resulting in corrosion of the pipe. To further protect them pipelines generally have a voltage applied to them (cathodic protection) so that they are at a negative potential relative to the ground. In this study, on a gas pipeline in New Zealand, we found that during a magnetic storm the changes in the ground potential due to the variations in the magnetic field were often large enough to override the cathodic protection so that the pipeline became positive relative to the ground. The orientation of the electric field that caused this does not agree with that expected from theory. This is due to the tectonic and geological structure of the area and illustrates that the risk presented to cathodic protection systems may be more severe than previously thought. Key Points: The cathodic protection potential on a New Zealand gas pipeline is found to vary significantly during a magnetic storm Contrary to simple theory, in this region the variations are found to be related to changes in the induced telluric field perpendicular to the pipeline This is a result of the electrical conductivity structure of the Earth associated with the tectonic setting of New Zealand